Visualization of stable ferritin complexes with palladium, rhodium and iridium nanoparticles detected by their catalytic activity in native polyacrylamide gels - Pekarik, Vladimir; Peskova, Marie; Guran, Roman; Novacek, Jiri; Heger, Zbynek; Tripsianes, Konstantinos; Kumar, Jitender; Adam, Vojtech (Dalton transactions (Cambridge, England, 2017)
The reductive discoloration of azo dye, Congo red, catalyzed by noble metal nanoparticles was used to visualize protein-metal complexes in native polyacrylamide gels after counterstaining with Coomassie blue. This technique was used to characterize the synthesis of palladium, rhodium and iridium nanoparticles encapsulated in Pyrococcus furiosus ferritin.